Pengaruh Penerapan Problem Based Learning Terhadap Prestasi Belajar Siswa SMP Islam Terampil NM NW Pancor Kopong - Fathurrahman (INOVASIA, 2022)
This study aims to determine the effect of the application of problem based learning on students' learning achievement in science. The population in this study were students of SMP Islam Skilled NM NW Pancor Kopong. The sample was class I which was taken randomly. In this study using a problem based learning model, this study uses a quantitative approach by using the type of experimental research. This study uses a posttest only control group design. The results of the analysis in this study indicate that the test data obtained a value of 0.71. If it is included in the test criteria, namely > , the data is not homogeneous and vice versa. The results of the hypothesis test carried out were of 4.06, Based on the Hypothesis Test, it was found that < then Ha was accepted and Ho was rejected with a significant level of 5% with = 1.99 and = 4.06.